How Accountability is Practiced in HKBP Church: An Empirical Evidence in Indonesia - Denny Andriana; Joe Putra Pratama Pardede; R. Nelly Nur Apandi (Fakultas Pendidikan Ekonomi dan Bisnis, 2022)
Prior studies report that accountability practice in a place of worship, i.e., church, is more to practicing sincerity and faith to God than to provide documents and transaction evidence. However, recent findings indicate that there is an increased fraud and embezzlement in churches. Using a stewardship theory, this study aims to explore the practice of accountability and transparency of a church’s financial activities from the perspective of its management and congregations. A HKBP church in Bandung, Indonesia, is chosen as the case study. A qualitative method is used in this study. The data obtained is through interviews, documentation, and observation. Key informants who participated in the interviews were the head of congregations, the treasurer and the treasury assembly staff. Also, three congregations were selected using purposive sampling to participate in responding to the questions. The findings show that the practice of accountability in the HKBP church is perceived good by its members. The involvement of congregations in decision making process in the church makes them satisfied with how the church is managed.